Essential pain pharmacology the prescriber's guide - Smith, Howard S. 1956- (Cambridge University Press, 2012)
Essential Pain Pharmacology: The Prescriber's Guide expertly reviews the most important medications used to relieve pain, now considered by many physicians as the fifth vital sign. The catalogue of analgesics has expanded rapidly, and this text presents the most up-to-date, comprehensive array of agents available for prescribing. Each clear and concise drug entry covers the range of indications, advantages and disadvantages, and tips for appropriate dosing and avoiding adverse effects. A separate section covers nutraceuticals, a class of drug increasingly used to manage chronic pain, yet little discussed in medical literature. The detailed description of each medication enables the user to make quick and informed decisions, confident that they are best serving the needs of their patients. Practical 'pearls' for each entry provide a quick go-to reference for the key information to consider before prescribing. This concise user-friendly reference is a must-have on the shelf of every physician.